Ultrafast multi-pulse transient absorption spectroscopy of fucoxanthin chlorophyll a protein from Phaeodactylum tricornutum - West, Robert G; Bína, David; Fuciman, Marcel; Kuznetsova, Valentyna; Litvín, Radek; Polívka, Tomáš (Biochimica et biophysica acta. Bioenergetics, 2018)
We have applied femtosecond transient absorption spectroscopy in pump-probe and pump-dump-probe regimes to study energy transfer between fucoxanthin and Chl a in fucoxanthin-Chl a complex from the pennate diatom Phaeodactylum tricornutum. Experiments were carried out at room temperature and 77 K to reveal temperature dependence of energy transfer. At both temperatures, the ultrafast (<100 fs) energy transfer channel from the fucoxanthin S2 state is active and is complemented by the second pathway via the combined S1/ICT state. The S1/ICT-Chl a pathway has two channels, the fast one characterized by sub-picosecond energy transfer, and slow having time constants of 4.5 ps at room temperature and 6.6 ps at 77 K. The overall energy transfer via the S1/ICT is faster at 77 K, because the fast component gains amplitude upon lowering the temperature. The pump-dump-probe regime, with the dump pulse centered in the spectral region of ICT stimulated emission at 950 nm and applied at 2 ps after excitation, proved that the S1 and ICT states of fucoxanthin in FCP are individual, yet coupled entities. Analysis of the pump-dump-probe data suggested that the main energy donor in the slow S1/ICT-Chl a route is the S1 part of the S1/ICT potential surface.
Keywords: Ultrafast spectroscopy; chlorofyl a; chlorofyl; spektrofotometrie atomová; xanthofyly; Spectrophotometry, Atomic; Diatoms; Energy transfer; Chlorophyll A; Carotenoids; Light-harvesting; Chlorophyll; Fucoxanthin-chlorophyll protein; rozsivky; Xanthophylls